The Sounds of Europe - Stolz, Thomas; Urdze, Aina; Otsuka, Hitomi (Lingua Posnaniensis, 2011)
This article is meant to demonstrate not only that it is possible technically but that it also makes sense linguistically to study phonological phenomena in a pan-European perspective. To prove our point, we employ the current comparative methodology associated with the framework of typologically-inspired areal linguistics. The data are evaluated quantitatively. We focus on the classes of velar and post-velar fricatives with phoneme status. Our investigation is based empirically on data drawn from a sample of 157 contemporary varieties spoken in Europe. Our results are indicative of a non-random distribution of the above classes of phonemes. Genetic, typological and areal factors are discussed as potential explanations of the observed geo-linguistic distribution of velar and post-velar fricatives on European soil. The general conclusion we draw is that it is high time to develop a research program which is dedicated to the continent-wide in-depth study of the phonological make-up of Europe.